Astaxanthin activated the SLC7A11/GPX4 pathway to inhibit ferroptosis and enhance autophagy, ameliorating dry eye disease - Hou, Chenting; Xiao, Jie; Wang, Youhai; Pan, Xinghui; Liu, Kangrui; Lu, Kang; Wang, Qing (Frontiers in Pharmacology, 2024)
Dry eye disease (DED) is a common eye disease in clinical practice. The crucial pathogenesis of DED is that hyperosmolarity activates oxidative stress signaling pathways in corneal epithelial and immune cells and, thus, produces inflammatory molecules. The complex pathological changes in the dry eye still need to be elucidated to facilitate treatment. In this study, we found that astaxanthin (AST) can protect against DED through the SLC7A11/GPX4 pathway. After treatment with AST, the SLC7A11/GPX4 pathway was positively activated in DED both in vivo and in vitro, accompanied by enhanced autophagy and decreased ferroptosis. In hyperosmolarity-induced DED corneal epithelial cells, AST increased the expression of ferritin to promote iron storage and reduce Fe2+ overload. It increased glutathione (GSH) and GPX4, scavenged reactive oxygen species (ROS) and lipid peroxide, and rescued the mitochondrial structure to prevent ferroptosis. Furthermore, inhibition of ferroptosis by ferrostatin-1 (Fer-1), iron chelator deferoxamine mesylate (DFO), or AST could activate healthy autophagic flux. In addition, in a dry eye mouse model, AST upregulated SLC7A11 and GPX4 and inhibited ferroptosis. To summarize, we found that AST can ameliorate DED by reinforcing the SLC7A11/GPX4 pathway, which mainly affects oxidative stress, autophagy, and ferroptosis processes.